ICE STORAGE CHARACTERISTICS OF CULTURED SILVER CARP - KUMAR, MONORANJAN; BASU, SUBRATA; HAZRA, A. (Journal of Indian Fisheries Association, 2015)
Cultured silver carp (Hypopthalmichthys molitrix 800-1000 g) wasstored in ice (fish to ice ratio 1:1) in a plywood box insulated with oneinch thick expanded poly styrene and subjected to detailed examinationof quality by chemical, microbilogical and organoleptic evaluation atregular intervals to asses the storage life in good acceptable form. Alphaaminonitrogen, non-protein nitrogen and pH values showed no positivecorrelation as spoilage index. Total volatile base nitrogen was not highat the end of the storage period although the fish became unacceptableÂ·during the period. There was steep decrease in total bacterial count duringinitial stages of storage and then incr-eased steadily on further storage.Organoleptic evaluation of raw and cooked meat revealed that fish wasin good acceptable form upto 14 days in ice.